The Integration of Religious Moderation Values in The Curriculum and Extracurricular Activities at Pesantren Darul Amanah - Adinugraha, Hendri Hermawan; Syakirunni’am, Luqman; Lawal, Uthman Shehu (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
This study explores the integration of religious moderation values within the formal curriculum and extracurricular activities at Pesantren Darul Amanah, Kendal, Central Java. The research aims to analyse how the principles of tawāsuṭ (moderation), tawāzun (balance), i’tidāl (justice), and tasāmuh (tolerance) are embedded in the school’s educational system and how these values influence students’ social attitudes. Using a qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews with teachers, administrators, and students, as well as a documentation analysis of curriculum and extracurricular programs. The findings reveal that the integration of religious moderation values is reflected explicitly in subjects such as Islamic Jurisprudence, Theology, and Islamic History, and implicitly in activities such as community service, inter-boarding school forums, and social projects. These integrations have strengthened students’ empathy, tolerance, and critical thinking skills, fostering inclusive and peaceful social interactions. The study concludes that Darul Amanah’s educational model demonstrates how Islamic boarding schools can promote religious moderation through pedagogical practices that balance spiritual, intellectual, and social development.